Growth, Electronic Structure, and Electrochemical Properties of Cubic BaTiO3 Synthesized by Low-Pressure Hydrothermal-Assisted Sintering - Bambang Soegijono; Gina Libria Nadjamoeddin; Mohammad Khotib; Zainal Alim Mas'ud (Universitas Gadjah Mada, 2022)
Cubic BaTiO3 was synthesized through low-pressure hydrothermal-assisted sintering using Ba(OH)2 and TiO2 as precursors with a mol ratio of Ba:Ti = 1.4:1. The single phase of cubic BaTiO3 was produced at a sintering temperature of 800 °C for 2, 4, 8, and 12 h. The absence of diffraction peak splitting at 2q of 45° was indicated cubic BaTiO3. The crystallite size of BaTiO3 ranged from 80–200 nm, and its size increased with increasing temperatures and sintering times. The micro-strain of the BaTiO3 crystal lattice had a range between 0.27 and 0.68%. The minimum bandgap on the indirect bandgap was about 1.75 eV from point M to Γ, while the direct bandgap was about 1.95 eV from Γ to Γ. Ti–O's interaction had a covalent character, while that of Ba–O had an ionic character based on the density of state (DOS) calculation. The characteristics of the BaTiO3 voltammogram show an irreversible redox mechanism with a more observable reduction peak in Ti4+/Ti3+. Higher current density at over potential indicated greater BaTiO3 capabilities in Oxygen Evolution Reaction (OER)-Oxygen Reduction Reaction (ORR) electrocatalysis. For that, purified cubic BaTiO3 offers potential application as an electrode for batteries, water splitting systems, and regenerative fuel cells.